Composition, processing, and quality control of whole flaxseed products used to fortify foods. Issue 1 (18th December 2022) - Zhang, Shan; Chen, Yashu; McClements, David Julian; Hou, Tao; Geng, Fang; Chen, Peng; Chen, Hongjian; Xie, Bijun; Sun, Zhida; Tang, Hu; Pei, Yaqiong; Quan, Shuang; et al.
Abstract: Whole flaxseed (flour) as a good source of omega‐3 fatty acid and phytochemicals with excellent nutritional and functional attributes has been used to enrich foods for health promotion and disease prevention. However, several limitations and contemporary challenges still impact the development of whole flaxseed (flour)‐enriched products on the global market, such as naturally occurring antinutritional factors and entrapment of nutrients within food matrix. Whole flaxseed (flour) with different existing forms could variably alter the techno‐functional performance of food matrix, and ultimately affect the edible qualities of fortified food products. The potential interaction mechanism between the subject and object components in fortified products has not been elucidated yet. Hence, in this paper, the physical structure and component changes of flaxseed (flour) by pretreatments coupled with their potential influences on the edible qualities of multiple fortified food products were summarized and analyzed. In addition, several typical food products, including baked, noodle, and dairy products were preferentially selected to investigate the potential influencing mechanisms of flaxseed (flour) on different substrate components. In particular, the altered balance between water absorption of flaxseed protein/gum polysaccharides and the interruption of gluten network, lipid lubrication, lipid–amylose complexes, syneresis, and so forth, were thoroughly elucidated. The overall impact of incorporating whole flaxseed (flour) on the quality and nutritional attributes of fortified food products, coupled with the possible solutions against negative influences are aimed. This paper could provide useful information for expanding the application of whole flaxseed (flour) based on the optimal edible and nutritional properties of fortified food products.